Integral assessment of productive and environmental parameters of a forage-based silvopastoral system - Arango, Jacobo; Sotelo Cabrera, Mauricio Efren; Gutiérrez Solís, Jhon Freddy; Hincapie, Belisario; Vázquez, Eduardo; Teutscherova, Nikola; Gaviria, Xiomara; Molina Botero, Isabel Cristina; Barahona Rosales, Rolando; Pulleman, Mirjam Margreet; Chirinda, Ngonidzashe; Peters, Michael (International Center for Tropical Agriculture, 2019)
Diversification of pastures and the incorporation of key plant functional groups (legumes) generally improve nutrient cycling and often lead to increased carbon sequestration in the soil. Furthermore, the inclusion of trees in the pastures improve soil properties while creating a microclimate more suitable for cattle, as well as for soil biological activity. Improved pastures with environmental benefits alongside with good management have vast potential to support region and country-level strategies to address relevant challenges related to the livestock sector in Latin America and the Caribbean (LAC) (Rao et al, 2015). The LivestockPlus project seeks to apply the concept of sustainable intensification of livestock systems in two countries of the LAC region such as Costa Rica and Colombia, to provide technical support, generate critical information and guidelines necessary for identifying options while contributing to planning and policies for scaling up of NAMAs.